Jews, Arabs and the Middle East - Broido, Ephraim; Poale Zion-Jewish Socialist Labour Party (London : Poale Zion, 1944)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: joden; Palestijnen; zionisme; Palestina; Midden-Oosten.